2021
DOI: 10.3390/jpm11111111
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Alexithymia, Dysmorphic Concern, and Exercise Addiction: The Moderating Effect of Self-Esteem

Abstract: As with other addictions, exercise addiction can severely impact individuals’ lives and have significant psychophysical consequences. Consequently, the study of the mechanisms involved in this psychopathological condition has great clinical and practical relevance. Therefore, the goal of the present study was to explore the risk factors and protective factors for exercise addiction, with a particular focus on the roles of alexithymia, body image concerns, and self-esteem. A sample of 288 regular exercisers (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…Such data may have great clinical relevance, suggesting that alexithymia and dissociation should be considered in the clinical assessment of the risk of pathological gambling behaviour. Indeed, both emotional dysregulation and high levels of dissociation have frequently been associated with psychopathology and lower mental resources [74][75][76][77][78], and they could be the focus of interventions aimed at reducing both the direct and indirect effects of alexithymia on problematic online gambling [79,80]. At the same time, the results also highlighted the importance of cohesion in this indirect path.…”
Section: Discussionmentioning
confidence: 99%
“…Such data may have great clinical relevance, suggesting that alexithymia and dissociation should be considered in the clinical assessment of the risk of pathological gambling behaviour. Indeed, both emotional dysregulation and high levels of dissociation have frequently been associated with psychopathology and lower mental resources [74][75][76][77][78], and they could be the focus of interventions aimed at reducing both the direct and indirect effects of alexithymia on problematic online gambling [79,80]. At the same time, the results also highlighted the importance of cohesion in this indirect path.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to the explanation of apparent common risk factors, towards even different addictions (physical exercise and alcohol), the association with the two different conditions could also be structured with different psychopathological and pathophysiological modalities. Gori et al [ 41 ] showed the positive relationship between alexithymia, exercise addiction, body image and self-esteem. Indeed, persons with alexithymia tend to have difficulty in managing their affect.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with POPU have in fact been described as having poor coping strategies and ineffective emotion regulation skills. 60,63 In this regard, although the literature highlights the etiological role of emotion dysregulation for both substance related 64,65 and behavioral addictions, 64,66,67 including the sexual one, 68 the data presented suggest that this can be further fueled by addictive behavior. The online pornography use can become problematic if used as a dysfunctional coping strategy for the regulation of affective states: this does not favor the development of more adaptive strategies in the subject, but on the contrary, stimulates a compulsive attitude towards cyberpornography feeding the state of dysregulation in the long term, in line with when the subject with sexual addiction is found.…”
Section: Discussionmentioning
confidence: 97%